2022
DOI: 10.3390/s22197410
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Regional Methane Emission Factors from Energy and Agricultural Sector Sources Using a Portable Measurement System: Case Study of the Denver–Julesburg Basin

Abstract: Methane (CH4), a powerful greenhouse gas (GHG), has been identified as a key target for emission reduction in the Paris agreement, but it is not currently clear where efforts should be focused to make the greatest impact. Currently, activity data and standard emission factors (EF) are used to generate GHG emission inventories. Many of the EFs are globally uniform and do not account for regional variability in industrial or agricultural practices and/or regulation. Regional EFs can be derived from top–down emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…A number of top‐down methane flux studies have been completed for the DM/NFR region. These include flux estimates based on two NOAA flights in late May 2012 (Pétron et al., 2014), two NOAA flights in March 2015 (Peischl et al., 2018), two University of Colorado (CU) and University of Maryland (UMD) flights in early October 2021 (Fried et al., 2022), a driving survey in the summer of 2021 (Riddick et al., 2022), and a University of Arizona satellite methane inversion analysis for June‐July and September‐October 2021 (Cusworth et al., 2022). The inversions used column‐average methane concentrations retrieved from the TROPOspheric Monitoring Instrument (TROPOMI).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of top‐down methane flux studies have been completed for the DM/NFR region. These include flux estimates based on two NOAA flights in late May 2012 (Pétron et al., 2014), two NOAA flights in March 2015 (Peischl et al., 2018), two University of Colorado (CU) and University of Maryland (UMD) flights in early October 2021 (Fried et al., 2022), a driving survey in the summer of 2021 (Riddick et al., 2022), and a University of Arizona satellite methane inversion analysis for June‐July and September‐October 2021 (Cusworth et al., 2022). The inversions used column‐average methane concentrations retrieved from the TROPOspheric Monitoring Instrument (TROPOMI).…”
Section: Resultsmentioning
confidence: 99%
“…These reductions occurred even though oil production increased by 343% and gas production by 297% from 2012 to 2020. In contrast, when the results from several short‐term, top‐down methane flux studies for the DJ Basin are considered on a timeline, they show a slight declining trend from 2012 to 2021 (Cusworth et al., 2022; Fried et al., 2022; Peischl et al., 2018; Pétron et al., 2014; Riddick et al., 2022). Possible reasons for discrepancies in methane trends will be discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of new extraction techniques, including the combination of horizontal drilling and hydraulic fracturing, new wells have continued to proliferate within the Julesburg Basin [ 41 ] ( Figures S3 and S4 ). Methane leaks from O&G infrastructure are treated as a point source, and are often analyzed using a Gaussian plume dispersion model [ 42 ]. Many of these wells are in close proximity to large population centers within this region, including the cities of Greeley, Cheyenne, and Denver.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Currently, bottomup methods estimate that 6 Tg of methane is lost from producing, processing, transmitting, storing, and distributing natural gas in the US each year [3]. Recent studies have shown differences between top-down and bottom-up methane emission estimates [4][5][6][7][8], and studies suggest bottom up approaches may miss some sources [6] or that emission factors derived decades ago may now be unrepresentative of current emissions processes [7,9,10].…”
Section: Introductionmentioning
confidence: 99%